S Gene Mutants Occurrence Among Hepatitis B Carriers in Malaysia - Suppiah, Jeyanthi (Hepat Mon, 2014)
BACKGROUND: The S gene region of the hepatitis B virus (HBV) codes for surface antigen (HBs Ag) and is responsible for classification of HBV strains. OBJECTIVES: The current study aimed to identify important mutations in the S gene in Hepatitis B virus (HBV) isolated from Malaysian HBV carriers. MATERIALS AND METHODS: Isolated HBV DNAs were subjected for PCR amplification and sequencing of HBV full genome. RESULTS: A total of 76 HBV full genome and 17 partial genome sequences were obtained from the 93 sequenced sera samples Genotyping of the full genome sequences by HEPSEQ software revealed a distribution of 49.46%, 48.39% and 2.15% of genotypes C, B, and D, respectively; whereas phylogenetic and jumping profile Hidden Markov Model (jpHMM) analysis identified six (7.89%) recombinant B/C strains. The distribution of sub-genotypes were B2 (78.79%) and B3 (21.21%) for genotype B, sub genotype D2 (100%) for genotype D and sub genotype C1 (75.76%), C2 (15.15%), C3 (6.06%) and C5 (3.13%) for genotype C. Mutation analysis in the S gene demonstrated two significant mutations which were W182 stop codon and deletion at open reading frame (ORF) of pre-S1 with the frequency occurrence of 2.2% (2/93) and 5.4% (5/93), respectively. The two patients with W182 stop codon were both male, infected with HBV genotype C and one showed progression of liver disease to hepatocellular carcinoma (HCC). CONCLUSIONS: Association with sex, genotype and clinical symptoms revealed that the pre-S1 ORF deletion occurred in 40% , 40%,and 20% of genotypes B,C, and D respectively, and 80% of the female population, of which all but one were diagnosed with chronic hepatitis B. Additionally, several mutations were found in the BCP region with the following incidence rate; C1653 T (8.6%), A1752 G (10.8%),1762 AGG--TGA 1764 (26.9%), C1766T(2.2%),T1768 A (10.8%), C1858 T (64.5%), G1896 A (25.8%).